Electrochemical Performance of Tellurium Oxide on TiO2/Ti Array for Photoelectrocatalytic Chemical Oxygen Demand Sensor Applications - Maulidiyah, Maulidiyah; Irwan, Irwan; Indriani, Annisa; Salim, La Ode Agus; Arham, Zul; Bijang, Catherina M.; Kurniawan, Kurniawan; Nurdin, Muhammad (Jurnal Rekayasa Kimia & Lingkungan, 2022)
The experiments were carried out using Te-TiO2/Ti as working electrodes, prepared by the simple anodization technique and dip coating method, on Ti substrates (TiO2/Ti). The measurements were performed in an electrochemical cell using a three-electrode system, with Te-TiO2/Ti as the working electrode, Ag/AgCl as the reference electrode and pt as the auxiliary electrode. A flow system for determining the profile and photocurrent response of reactive orange 84 was developed using Linear Sweep Voltammetry (LSV) and Multi-Pulse Amperometry (MPA). The physicochemical properties of Te-TiO2/Ti electrodes have been studied using UVvis DRS analysis techniques and compared with un-doped TiO2/Ti electrodes. The UVvis DRS showed that the TiO2/Ti doped Te functionally decreases bandgap to 3.0 eV. The results showed that the photocurrent of reactive orange 84 was observed in the concentration range (1-5 M), with a linear response between concentration and charge.